Involvement of epithelial-mesenchymal transition afforded by activation of LOX-1/ TGF-β1/KLF6 signaling pathway in diabetic pulmonary fibrosis. (June 2017) - Zou, Xiao-Zhou; Gong, Zhi-Cheng; Liu, Ting; He, Fang; Zhu, Tian-Tian; Li, Dai; Zhang, Wei-Fang; Jiang, Jun-Lin; Hu, Chang-Ping
Abstract: Background and objective: Diabetic pulmonary fibrosis is a severe disease that increases mortality risk of diabetes. However, the molecular mechanisms leading to pulmonary fibrosis in diabetes are poorly understood. This study investigated the roles of epithelial-mesenchymal transition (EMT) and the associated molecular mechanisms in streptozotocin (STZ)-induced rat pulmonary fibrosis. Methods: The rat model of diabetic pulmonary fibrosis was established by intraperitoneal injection of a single dose of STZ (35 mg/kg). Typical lesions of diabetic pulmonary fibrosis were observed 8 weeks after STZ injection by hematoxylin-eosin (HE) and Masson staining. Human bronchial epithelial cells (HBECs) and A549 cells were treated by high glucose. Gene or protein expression was measured by real-time PCR, Western blot, immunohistochemistry or immunofluorescence. The knockdown of lectin-like oxidized low density lipoprotein receptor-1 (LOX-1) or transforming growth factor-β1 (TGF-β1) was conducted by siRNA. Results: Activation of EMT was observed in lung tissues of STZ-induced diabetic rats, exhibiting a loss in the epithelial cell marker E-cadherin and an increase in the mesenchymal marker Vimentin. The protein and mRNA levels of LOX-1, TGF-β1 and krüppel-like factor 6 (KLF6) in the lung tissues were increased. Incubation of HBECs and A549 cells with high glucose activated EMT and induced an increase in LOX-1, TGF-β1 and KLF-6 expression. LOX-1 siRNA inhibited high glucose-induced EMT in HBECs and A549 cells, which correlated with the reduction of TGF-β1. TGF-β1 siRNA decreased the expression of LOX-1 and KLF6. Conclusions: EMT was involved in the pathological process of diabetic pulmonary fibrosis, which was activated by LOX-1/TGF-β1/KLF6 signaling pathway.